Dampak emosi pada perkembangan sosial anak: Membangun keterampilan interpersonal sejak dini - Arifah, Elvi Nisaul (Maliki Interdisciplinary Journal, 2025)
This study is motivated by the importance of understanding the role of emotions in children’s social development, particularly in building interpersonal skills from an early age. The problem discussed in this study is how various aspects of emotions, such as expression, regulation, and understanding, affect children’s social abilities in interacting with their environment. The purpose of this study is to provide an in-depth overview of the impact of emotions on children’s social skills and how parents and the environment can help them develop healthy interpersonal skills. Based on the discussion, it was found that children’s ability to recognize and manage their emotions significantly contributes to the success of social interactions in the family, school, and community